2019
DOI: 10.1021/acsnano.9b03053
|View full text |Cite
|
Sign up to set email alerts
|

Probing and Controlling Dynamic Interactions at Biomolecule–Nanoparticle Interfaces Using Stochastic DNA Walkers

Abstract: Herein, we report a bottom-up approach to assemble a series of stochastic DNA walkers capable of probing dynamic interactions occurring at the bio–nano interface. We systematically investigated the impact of varying interfacial factors, including intramolecular interactions, orientation, cooperativity, steric effect, multivalence, and binding hindrance on enzymatic behaviors at the interfaces of spherical nucleic acids. Our mechanistic study has revealed critical roles of various interfacial factors that signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…Engineering the surface chemistry is critical for rapid DNA walking. 125 Li and coworkers found that threshold values exist for DNA walker density with specific lengths. 116 Increasing the number of walkers from 0 to 20 per nanoparticle accelerated the reaction, while a further increase to 60 decreased the signal.…”
Section: Fluorescence Sensing Using Aunps As Quenchersmentioning
confidence: 99%
“…Engineering the surface chemistry is critical for rapid DNA walking. 125 Li and coworkers found that threshold values exist for DNA walker density with specific lengths. 116 Increasing the number of walkers from 0 to 20 per nanoparticle accelerated the reaction, while a further increase to 60 decreased the signal.…”
Section: Fluorescence Sensing Using Aunps As Quenchersmentioning
confidence: 99%
“…75 Recent advances in fluorescent-based assays incorporating plasmonic nanoparticles include the development of DNA walkers, where binding of one target molecule initiates the cleavage or release of multiple biomolecularly linked fluorophore probes. 76 This methodology can potentially enhance the sensitivity and lower the LOD dramatically, as shown in the detection of the tuberculosis gene with an increase in sensitivity by ∼100 times. 77 On the other hand, surface-enhanced (resonance) Raman scattering SE(R)-RS provides ultrahigh sensitivity at the single-molecule level while negating the limitations of photobleaching in fluorescence-based techniques.…”
Section: ■ Recent Progressmentioning
confidence: 99%
“…Electrochemical techniques combined with the specific CRISPR/Cas system have the potential to mitigate the key challenge of POC diagnostics due to its attractive features, including high sensitivity, rapid signal readout, simple and cost-effective transduction elements, easy integration with additional components, and the potential for miniaturization. Despite their great success, they suffer from some limitations as follows. In contrast to optical approaches operated in a homogeneous solution, the reported electrochemical biosensing platforms require probe surface immobilization and, more importantly, elaborate the optimization of surface chemistry and coverage; however, such laborious optimization and time-consuming manipulation are not competitive to fulfill the repeatability of analysis and the requirements of POC. Also, the environment-sensitive configurational freedom of the surface-bound probe is swayed, ascribing to the steric hindrance effect on the heterogeneous interface, resulting in decreased orientation/accessibility. Particularly, these developed electrochemical biosensing platforms have a “signal-off” architecture, which is hard to provide guarantee for sensitivity and reproducibility because of limited signal gain and microenvironmental interferences from substrates and systems . In view of the above, we are interested in developing an immobilization-free electrochemical biosensing platform that uses the CRISPR/Cas system as a biomolecular component for sensing-dependent response to overcome the above limitations.…”
Section: Introductionmentioning
confidence: 99%